Potentially Preventable Hospitalizations Among Older Adults: 2010-2014 - Mahmoudi, Elham (Ann Fam Med, 2020)
PURPOSE: We undertook a study to examine national trends in potentially preventable hospitalizations—those for ambulatory care–sensitive conditions that could have been avoided if patients had timely access to primary care—across 3,200 counties and various subpopulations of older adults in the United States. METHODS: We used 2010-2014 Medicare claims data to examine trends in potentially preventable hospitalizations among beneficiaries aged 65 years and older and developed heat maps to examine county-level variation. We used a generalized estimating equation and adjusted the model for demographics, comorbidities, dual eligibility (Medicare and Medicaid), ZIP code–level income, and county-level number of primary care physicians and hospitals. RESULTS: Across the 3,200 study counties, potentially preventable hospitalizations decreased in 327 counties, increased in 123 counties, and did not change in the rest. At the population level, the adjusted rate of potentially preventable hospitalizations declined by 3.45 percentage points from 19.42% (95% CI, 18.4%-20.5%) in 2010 to 15.97% (95% CI, 15.3%-16.6%) in 2014; it declined by 2.93, 2.87, and 3.33 percentage points among White, Black, and Hispanic patients to 14.96% (95% CI, 14.67%-15.24%), 17.92% (95% CI, 17.27%-18.58%), and 17.10% (95% CI, 16.25%-18.0%), respectively. Similarly, the rate for dually eligible patients fell by 3.71 percentage points from 21.62% (95% CI, 20.5%-22.8%) in 2010 to 17.91% (95% CI, 17.2%-18.7%) in 2014. (P <.001 for all). CONCLUSIONS: During 2010-2014, rates of potentially preventable hospitalization did not change in the majority of counties. At the population level, although the rate declined among all subpopulations, dually eligible patients and Black and Hispanic patients continued to have substantially higher rates compared with non–dually eligible and White patients, respectively.